The effects ofsunnah foods on nutritional status / Nurul Syafinaz Ramli - Ramli, Nurul Syafinaz (2016)
Malnutrition is a condition either nutrients deficiency or excess that consists of imbalance of energy, protein and other nutrients that result in adverse effects on tissue or body fonn, physiology and clinical outcome. Nutritional status can be divided into three groups; well nourished, moderately nourished and malnourished and severely malnourished.. In Islam, there are many commands that direct the believers to the necessity of keeping the physical body healthy so that the soul and spirit also remain healthy. In the perspective of education, the Muslim adolescents do not fmd the linkage of the sunnah with their education, therefore the sunnah become quite rare to the education system. This also applicable in adults. Thus, this study is crucial in identifying the effects of sunnah foods on nutritional status as well in educating the sunnah foods practice in the population specifically the adults population at Klang Valley, Selangor, Malaysia. Sample of 50 respondents was collected with anthropometry, biochemical and clinical assessment as the parameters. The data was analyzed to evaluate and to determine the correlation between the practicing of sunnah foods with the nutritional status and the effects of sunnah foods on nutritional status. This study suggested that the practicing of sunnah foods such as dates, honey, black seeds and milk have correlation with the Body Mass Index (BMI) and blood glucose. However, this study suggested that the practicing of sunnah foods give no correlation with body fat percentage and blood pressure. It is hope this study can give insight that sunnah foods are important in affecting our nutritional status and more efforts should be done in order to incorporate this healthy culture in the community